2021
DOI: 10.3389/fonc.2021.660051
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PEWS on Perceived Quality of Care During Deterioration in Children With Cancer Hospitalized in Different Resource-Settings

Abstract: BackgroundChildren with cancer are at high risk for clinical deterioration and subsequent mortality. Pediatric Early Warning Systems (PEWS) have proven to reduce the frequency of clinical deterioration in hospitalized patients. This qualitative study evaluates provider perspectives on the impact of PEWS on quality of care during deterioration events in a high-resource and a resource-limited setting.MethodsWe conducted semi-structured interviews with 83 healthcare staff (nurses, pediatricians, oncology fellows,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 20 publications
(27 reference statements)
1
20
0
Order By: Relevance
“…Our study demonstrates multiple benefits of PEWS implementation for patients, clinicians, healthcare teams, and institutions and the ways in which these benefits modulate and reinforce one another. Similar to prior studies, we found that staff perceived PEWS to reduce adverse events (8), improve quality-of-care (9), increase staff knowledge, confidence, and empowerment (10), improve interprofessional and interdisciplinary communication (11), and reduce hospital costs (13). Our study, however, additionally demonstrates that improvements in patient outcomes increase staff motivation and job satisfaction, and better interpersonal relationships foster an improved work environment leading to changes in hospital culture including increased emphasis on patient-centered care, patient safety, and quality improvement.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study demonstrates multiple benefits of PEWS implementation for patients, clinicians, healthcare teams, and institutions and the ways in which these benefits modulate and reinforce one another. Similar to prior studies, we found that staff perceived PEWS to reduce adverse events (8), improve quality-of-care (9), increase staff knowledge, confidence, and empowerment (10), improve interprofessional and interdisciplinary communication (11), and reduce hospital costs (13). Our study, however, additionally demonstrates that improvements in patient outcomes increase staff motivation and job satisfaction, and better interpersonal relationships foster an improved work environment leading to changes in hospital culture including increased emphasis on patient-centered care, patient safety, and quality improvement.…”
Section: Discussionsupporting
confidence: 87%
“…The impacts of PEWS have been demonstrated across multiple levels of hospital care. PEWS decrease clinical deterioration events and pediatric intensive care unit (PICU) utilization ( 8 ), and improve the perceived quality of care ( 9 ). PEWS have also been shown to foster nursing empowerment and increase confidence in recognizing and managing clinical deterioration ( 10 ), improve interdisciplinary communication and relationships ( 11 , 12 ), and lead to cost savings ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Implementation of PEWS improves patient outcomes, reduces the cost of care, and optimizes interdisciplinary communication in resource-limited hospitals. [10][11][12][13][14][15][16] Despite evidence of their benefits, PEWS are not widely used in hospitals with resource limitations. 5 Although reasons for this practice gap are multidimensional, resource-limited hospitals likely experience specific barriers to implementation of evidence-based practices, and challenges implementing PEWS may discourage their use in these settings.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the diagnosis of potential sepsis cases is the cornerstone of therapeutic practice, a more structured and relatively objective approach is required to minimize human-related factors that could result in potential sepsis cases being missed. Such efforts led to the proposal of the PEWS system, which is widely accepted and has been validated in different settings with the potential benefit of identifying sepsis cases earlier and thus improving outcomes 1 , 9 , 20 . However, compliance with PEWS and integrated bundles requires reliable performance, high compliance, and regular audits, which could be challenging and resource demanding due to human factors 9 , 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%